Menyelami Dampak Modernisasi Pesantren (Antara Kebutuhan dan Tuntutan) - Hasanah, Amalia; Anshory, Muhammad Isa (TSAQOFAH, 2024)
Islamic boarding schools as one of the oldest education that was born and grew and developed in Indonesia has a very important role, both for the advancement of Islamic education and for the Indonesian nation. In the history of Indonesia's struggle for independence, pesantren was one of the spearheads in fighting the colonialists. However, nowadays, pesantren are better understood as a group that only studies religion and classical books, so that for general knowledge they are considered behind. The world of students is also sometimes still considered a closed or exclusive world so that it is considered backward in the face of the development of the modern world. Society views that the times have developed towards the era of globalization, so pesantren are required to be able to adjust to these changes, so that after graduating from pesantren, students are not only experts in the field of religion but are able to adjust to the times. With these demands, modern pesantren emerged that included many aspects of modernization, for example including information technology or the freedom of access to social media. Based on this presentation, the author is interested in examining whether the entry of modernity into pesantren is an advance or a threat, so the purpose of this study is to see the extent to which modernity affects teaching in pesantren. This research uses qualitative research methods with a literature model. The stages in analyzing data are doing it by reducing data, presenting data and drawing conclusions.